Gene Expression and Yeast Two-Hybrid Studies of 1R-MYB Transcription Factor Mediating Drought Stress Response in Chickpea (Cicer arietinum L.) - Ramalingam, Abirami; Kudapa, Himabindu; Pazhamala, Lekha T.; Garg, Vanika; Varshney, Rajeev K. (Frontiers in Plant Science, 2015)
Drought stress has been one of the serious constraints affecting chickpea productivity to a great extent. Genomic assisted breeding in chickpea has been effective in providing a yield advantage of up to 24 %, thus having a potential to accelerate breeding precisely and efficiently. In order to do so, understanding the molecular mechanisms for drought tolerance and identification of candidate genes are crucial. Transcription factors (TFs) have important roles in the regulation of plant stress related genes. In this context, quantitative real time-PCR (qRT-PCR) was used to study the differential gene expression of selected TFs, identified from large-scale gene expression analysis, in contrasting drought responsive genotypes. Root tissues of ICC 4958 (tolerant), ICC 1882 (sensitive), JG 11 (elite) and JG 11+ (introgression line) were used for the study. Subsequently, a candidate single repeat MYB gene (1R-MYB) that was remarkably induced in the drought tolerant genotypes under drought stress was cloned and subjected to Y2H analysis by screening a root cDNA library. The protein-protein interaction study identified three interacting peptides, a galactinol-sucrose galactosyltransferase 2, a CBL (Calcineurin B-like)-interacting serine/threonine-protein kinase 25 and an ABA responsive 17-like, which were confirmed by the co-transformation of candidate plasmids in yeast. These findings provide preliminary insights into the ability of 1R-MYB TF to co-regulate drought tolerance mechanism in chickpea roots.